Effect of Majapahit (Crescentia cujete L.) fruit powder on the immune profile of Litopenaeus vannamei after infection with Vibrio spp - Rahmaningsih, Sri (Vet World, 2021)
BACKGROUND AND AIM: The use of bioactive compounds is a promising tool to improve shrimp health regarding vibriosis. This study aimed to determine the effect of the dietary Majapahit (Crescentia cujete L.) fruit powder on the cellular immune response of vannamei shrimp (Litopenaeus vannamei) infected with Vibrio harveyi, Vibrio alginolyticus, and Vibrio parahaemolyticus. MATERIALS AND METHODS: Twelve vannamei shrimp (aged 1 month) were randomly divided into four groups (n=3). Vannamei shrimp received experimental feed with different concentrations of Majapahit fruit powder for 20 days: Group A, 0%; Group B, 3.04%; Group C, 6.08%, and Group D, 9.12%. Subsequently, vannamei shrimp was infected with V. harveyi, V. alginolyticus, and V. parahaemolyticus. The total hemocytes, total differential hemocytes (hyaline, semi-granular, and granular cells), and phagocytic activity were assessed. Data were analyzed through analysis of variance (p<0.05) using SPSS ver. 24 for Windows. RESULTS: Majapahit fruit powder at a dose of 3.04% increased the number of hyaline cells of L. vannamei after infection with Vibrio spp. Supplementation of the feed formula with Majapahit fruit powder at a dose of 3.04% increased the number of semi-granular and granular cells compared with the control. Furthermore, Majapahit fruit powder at doses of 3.04% and 6.08% increased the hemocytes compared with a dose of 9.12%. The phagocytic activity of L. vannamei after infection with Vibrio spp. tends to increase after supplementation with 3.04% Majapahit fruit powder. CONCLUSION: This study showed that the addition of C. cujete L. powder to the feed formula increased the cellular immune response. The most effective dose ranged from 3.04% to 6.08%.